The Crucible : An Autobiography by Colonel Yay, Filipina American Guerrilla - Panlilio, Yay, 1913-1978 (Book collections on Project MUSE., 2010)
In this 1950 memoir, The Crucible: An Autobiography by Colonel Yay, Filipina American Guerrilla, Panlilio narrates her experience as a journalist, triple agent, leader in the Philippine resistance against the Japanese, and lover of the guerrilla general Marcos V. Augustin, from the war-torn streets of Japanese-occupied Manila, to battlegrounds in the countryside, and the rural farmlands of central California. Denise Cruz's introduction imparts key biographical, historical, and cultural contexts.